Polyethylene Film Surface Modification via Benzoic Acid Grafting - Grafia, Ana Luisa (2024)
A polyethylene (PE) film surface modification method is proposed via benzoic acid (BA)alkylation grafting to improve the surface affinity to polar substances. The procedure involves sequentially spraying AlCl3 and BA onto the heat-softened PE surface. The occurrence of the alkylation reaction was evaluated through comparative chemical, morphological, and thermal analyses. It was demonstrated that the grafting reaction of BA onto the PE film surface took place, limited to the surface layer, while preserving the bulk properties of PE. The reaction resulted in the formation of aluminum benzoate complexes, which improved the surface affinity to polar compounds. The impact of grafting on the surface properties of PE was further assessed by comparing the behavior of PE films treated with BA and untreated PE films when painted with watercolors. The PE film grafted with BA exhibited increased affinity towards watercolors, providing strong evidence of a change in surface polarity from hydrophobic to hydrophilic. These findings indicate that the proposed methodology effectively renders the PE surface paintable, even with non-toxic water-based inks, making it suitable for applications such as packaging.